How do former medical and nursing undergraduates describe their learning on an interprofessional training Ward 12-18 months later?: a retrospective qualitative analysis - Mink, Johanna; Zurek, Bianka; Götsch, Burkhard; Mihaljevic, André L.; Mitzkat, Anika; Trierweiler-Hauke, Birgit; Mahler, Cornelia (BMC medical education, 2023)
Interprofessional training wards (IPTWs) seem to deliver good results in terms of development of interprofessional competencies. However, evidence of long-term effects of these training wards on learners’ competency development is lacking and little is known about retrospective evaluation of IPTWs. Therefore, this study aimed to explore the retrospective evaluation of competency development and interprofessional collaboration of former undergraduates 12 or more months after a placement on an IPTW.